In-beam spectroscopy of â ·Â²Ge - Henninger, Katharine Rose (Rhodes University, Faculty of Science, Department of Physics, 2012)
The high-spin states of the nucleus â ·Â²Ge were populated via the â ·Â°Zn(a,2n)â ·Â²Ge fusion-evaporation reaction at a beam-energy of 30 MeV. The ')'-decays were observed with the AFRODITE spectrometer array at iThemba LABS (Faure, South Africa). Twenty-seven new transitions, 18 new levels and 2 new bands were added to the â ·Â²Ge level scheme, and several corrections were made to t he previously-known level scheme. Transitions were characterised using Directional Correlation from Oriented states (DCO) and polarisation measurements, and spin-parity assignments were made for 7 new levels. Spin and parity were also reassigned to a previously-known structure. One of the new bands was ident ified as part of an octupole-vibrational band. No tetrahedral states were observed in the scheme despite N = 40 and Z = 32 having been identified as tetrahedral magic numbers. The meaning of the new 14â º yrast level for the underlying structure of the ground state band is discussed
Keywords: Nuclear shapes; Hyperfine structure